A method for preparing high-resilience graphene foam film
By adjusting the mixed solvent composition of the reducing agent and controlling the pore size distribution of the graphene foam film, the problem of poor compression resilience performance of the graphene foam film in traditional processes is solved, and high resilience and excellent thermal conductivity are achieved.
Patent Information
- Application Number
- CN202510116110.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Traditional preparation processes are difficult to improve the compression resilience performance of graphene foam film, resulting in uneven pore size distribution and poor compression performance.
By adjusting the composition of the mixed solvent of the reducing agent, tert-butanol and hydrazine hydrate are dissolved in the mixed solvent, the foaming process of graphene oxide is controlled, and a graphene foam film with narrow pore size distribution and small average pore size is formed.
It significantly improves the compression resilience performance of the graphene foam film, forms a fine pore structure, improves the compression resistance and resilience of the material, and improves the conductivity and thermal conductivity in the vertical direction.
Smart Images

Figure CN119551666B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of graphene films, in particular to a method for preparing a high-resilience graphene foaming film. Background Art
[0002] As a two-dimensional carbon nanomaterial, graphene has shown extensive application potential in many fields with its excellent physical and chemical properties. It has the characteristics of high specific surface area, high Young's modulus, high electron mobility and excellent thermal conductivity. In key fields such as new energy, thermal management, wave absorption, and electromagnetic shielding, the application prospects of graphene are widely optimistic. In particular, the porous structure of graphene, on the one hand, inherits the high specific surface area and rich pores of graphene, and on the other hand, gives full play to the high electrical and thermal conductivity of graphene, making it a great concern in the fields of energy, catalysis, and composite materials.
[0003] Although porous graphene membranes have shown great potential in many applications due to their unique structure and properties, they still face some challenges in practical applications. The preparation of porous graphene membranes using graphene oxide as raw material often has problems such as wide pore size distribution and poor compression rebound. This is because the removal rate of the abundant oxygen-containing groups on the surface of graphene oxide is difficult to control, and a large amount of gas escapes quickly, resulting in the appearance of large pore structures inside the membrane. The appearance of large pores causes the groups on the surrounding graphene sheets to be removed and then escape from the large pores, further expanding the large pores and generating small pores around the large pores. These large pores will undergo irreversible collapse when compressed, which in turn affects the overall compression strength and rebound performance of the material. In addition, due to the two-dimensional orientation characteristics of the graphene membrane, the gas tends to escape along the horizontal direction of the membrane, resulting in most pore structures being flat, which is also not conducive to compression performance. Summary of the invention
[0004] In view of the problem that the current traditional preparation process is difficult to improve the compression rebound performance of graphene foam film, the present invention provides a method for preparing a high-rebound graphene foam film. By adjusting the mixed solvent composition of the reducing agent, the rapid reduction foaming is inhibited to prepare a graphene foam film with a narrow pore size distribution and a small average pore size. The film exhibits excellent compression rebound performance and can be used as an elastic skeleton in composite materials, thermal interface materials, electrode materials and other scenarios.
[0005] Specifically, the present invention adopts the following technical solution: a method for preparing a high-resilience graphene foam film, comprising the following steps:
[0006] (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 1-10:100, and the mass ratio of tert-butyl alcohol to water is 2-10:1;
[0007] (2) Soaking the graphene oxide film in the mixed solution obtained in step (1) at 20-40° C. for 10-30 min to obtain a foamed wet film;
[0008] (3) drying the foamed wet film obtained in step (2), reducing it at a low temperature of 150-200°C for 10-24 h, then placing it in a nitrogen atmosphere, heating it to 1300°C at a rate of 5°C / min and keeping it at that temperature for 1-3 h, and cooling it naturally to obtain a foamed carbonized film;
[0009] (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000-2600°C at 5°C / min for high temperature treatment for 0.5-3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.
[0010] Tert-butanol is a weakly polar molecule, and its interaction with graphene oxide is weak, so it can only partially swell graphene oxide. After tert-butanol and water are miscible, the overall polarity of the mixed solution decreases, resulting in the limitation of the free movement of graphene oxide sheets in the mixed solvent. In addition, the ability of hydrazine hydrate to contact graphene oxide also decreases, so that it cannot deform quickly during the foaming process to produce a large pore structure. In addition, due to the swelling effect, graphene oxide forms a wrinkled structure in the vertical direction, so that the gas no longer relies purely on the horizontal escape channel, and it is easy to form a pore structure that is closer to a circle (such as Figure 2 This narrow distribution and nearly circular pores have better compression resistance and rebound performance.
[0011] Furthermore, the thickness of the graphene oxide film in step (2) is 10-100 μm. If the graphene oxide film is too thin, its own strength will be too low after foaming and it will be easy to break; if the film is too thick, the pores on the upper and lower surfaces will be larger due to more thorough foaming reaction, and the pores will be smaller as they approach the center, resulting in uneven pores in the vertical direction.
[0012] Furthermore, the carbon-oxygen ratio of the graphene oxide film in step (2) is not greater than 15. If the carbon-oxygen ratio of graphene oxide is too high, it cannot provide oxygen-containing functional groups required for foaming, thereby affecting the foaming effect. Preferably, the carbon-oxygen ratio of the graphene oxide film in step (2) is 3.5-6.
[0013] Furthermore, in step (2), the mass ratio of the graphene oxide membrane to the mixed solution is not greater than 10%. Too much addition of the graphene oxide membrane and insufficient foaming agent will lead to insufficient reaction inside the membrane and uneven pore size distribution.
[0014] Furthermore, the graphene oxide film in step (2) is obtained by extruding or casting a graphene oxide slurry and then drying it.
[0015] Furthermore, the drying method in step (3) is one or more combinations of natural air drying, infrared heating drying, and hot air drying.
[0016] Furthermore, the inert gas in step (3) is one of nitrogen and argon, or a mixture thereof.
[0017] Beneficial effects of the present invention:
[0018] (1) Significantly improve the compression resilience of graphene foam film: By introducing low-polarity tert-butyl alcohol, on the one hand, the mobility of graphene oxide is reduced, and on the other hand, the ability of hydrazine hydrate to contact with graphene oxide is reduced, thus avoiding the problem of uneven pore size distribution inside the graphene film caused by rapid reduction of hydrazine hydrate. A fine pore structure is formed, which improves the overall compression resistance and resilience of the material.
[0019] (2) Significantly improve the electrical and thermal conductivity of the material in the vertical direction: The internal pores of conventional foam films are mostly large-sized flat structures, and no effective network structure is built in the vertical direction. In contrast, the material obtained by the present invention constructs a more efficient three-dimensional vertical network, which has unique advantages in application scenarios such as thermal interfaces, sensors, and phase change energy storage.
[0020] (3) Simple operation: Adding a certain amount of tert-butyl alcohol to the conventional hydrazine hydrate reduction makes the process easy to implement and the cost is controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a low-magnification microscopic image of a cross-section of the material obtained in Example 1 by scanning electron microscopy (SEM);
[0022] Figure 2 This is a high-magnification microscopic image of a cross-section of the material obtained in Comparative Example 1 by scanning electron microscope (SEM);
[0023] Figure 3 The pore size distribution diagram of Example 1 and Comparative Example 1 in the range of 10 to 2000 μm;
[0024] Figure 4 is the compression-rebound curve of Example 1;
[0025] Figure 5 This is the compression-rebound curve of Comparative Example 1. DETAILED DESCRIPTION
[0026] The embodiments of the present invention are further described below with reference to a plurality of embodiments.
[0027] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0028] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.
[0029] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. The terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first" and "second" can explicitly or implicitly include one or more of the features.
[0030] In the description of the present invention, “plurality” means two or more than two, unless clearly defined otherwise.
[0031] In the description of the present invention, it should be understood that the terms "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0032] As is common knowledge in the art, the pore size is calculated by analyzing the SEM image using Image J software; the coefficient of dispersion refers to the ratio of the standard deviation to the mean; the vertical thermal conductivity is tested using the laser flash method, using the German NETZSCH LFA467 equipment, and a vertical fixture for testing.
[0033] Example 1
[0034] (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 10:100, and the mass ratio of tert-butyl alcohol to water is 3:1;
[0035] (2) soaking a graphene oxide film having a thickness of 50 μm and a carbon-oxygen ratio of 3.5 in the mixed solution obtained in step (1), wherein the mass ratio of the graphene oxide film to the mixed solution is 1:100, and maintaining the mixture at 20° C. for 30 min to obtain a foamed wet film;
[0036] (3) The foamed wet film obtained in step (2) was naturally air-dried, and low-temperature reduced at 150°C for 24 h, and then placed in a nitrogen atmosphere, heated to 1300°C at 5°C / min and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film;
[0037] (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000°C at 5°C / min for 3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.
[0038] The microscopic morphology of the cross section of the obtained graphene foam film is as follows: Figure 1 and Figure 2 As shown in the figure, it can be found that the inside is a three-dimensional network structure formed by overlapping graphene sheets, which contains a large number of holes with relatively uniform sizes. The graphene sheets around the holes are connected to form a continuous structure. In contrast, the inside of the graphene membrane reduced with hydrazine hydrate is mainly flat pores with uneven sizes ( Figure 2 ). Figure 3 The pore size distribution of Example 1 and Comparative Example 1 in the range of 10 to 130 microns is shown in Figure 2. The dispersion coefficient of the pore size distribution of Example 1 is 0.57, and that of Comparative Example 1 is 0.81, which proves that the pore size distribution of Example 1 is more uniform. Figure 4 As shown in the figure, under 50% strain compression, its irreversible compression is about 6%, indicating that it has high compression rebound ability. In contrast, the graphene film reduced by hydrazine hydrate has an irreversible compression of 26%, and its ability to recover shape after compression is poor. The vertical thermal conductivity of the obtained graphene foam film is 67 W / m K, which is higher than the vertical thermal conductivity of Comparative Example 1 (25 W / m K).
[0039] Example 2
[0040] (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 20:100, and the mass ratio of tert-butyl alcohol to water is 2:1;
[0041] (2) soaking a graphene oxide film having a thickness of 10 μm and a carbon-oxygen ratio of 3.5 in the mixed solution obtained in step (1), wherein the mass ratio of the graphene oxide film to the mixed solution is 1:100, and maintaining the mixture at 20° C. for 20 min to obtain a foamed wet film;
[0042] (3) The foamed wet film obtained in step (2) was naturally air-dried, and low-temperature reduced at 150°C for 24 h, and then placed in a nitrogen atmosphere, heated to 1300°C at 5°C / min and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film;
[0043] (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000°C at 5°C / min for 3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.
[0044] The pore size distribution dispersion coefficient of the obtained graphene foam film in the range of 10~130 microns is 0.64. Under 50% strain compression, its irreversible compression is about 10%, and its vertical thermal conductivity is 58 W / m K.
[0045] Example 3
[0046] (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 1:100, and the mass ratio of tert-butyl alcohol to water is 3:1;
[0047] (2) soaking a graphene oxide film having a thickness of 10 μm and a carbon-oxygen ratio of 3.5 in the mixed solution obtained in step (1), wherein the mass ratio of the graphene oxide film to the mixed solution is 1:100, and maintaining the mixture at 40°C for 10 min to obtain a foamed wet film;
[0048] (3) The foamed wet film obtained in step (2) was dried by infrared heating, and then reduced at 200 °C for 24 h. Then, the film was placed in an argon atmosphere, heated at 5 °C / min to 1300 °C and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film.
[0049] (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000°C at 5°C / min for 3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.
[0050] The pore size distribution dispersion coefficient of the obtained graphene foam film in the range of 10~130 microns is 0.46. Under 50% strain compression, its irreversible compression is about 5%, and the vertical thermal conductivity is 73 W / m K.
[0051] Example 4
[0052] (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 20:100, and the mass ratio of tert-butyl alcohol to water is 2:1;
[0053] (2) soaking a graphene oxide film with a thickness of 100 μm and a carbon-oxygen ratio of 6 in the mixed solution obtained in step (1), wherein the mass ratio of the graphene oxide film to the mixed solution is 1:100, and maintaining the mixture at 20°C for 30 min to obtain a foamed wet film;
[0054] (3) The foamed wet film obtained in step (2) was dried by infrared heating, and then reduced at 200 °C for 10 h. Then, the film was placed in a nitrogen atmosphere, heated at 5 °C / min to 1300 °C and kept at that temperature for 3 h, and then cooled naturally to obtain a foamed carbonized film.
[0055] (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2600°C at 5°C / min for high temperature treatment for 0.5 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.
[0056] The pore size distribution dispersion coefficient of the obtained graphene foam film in the range of 10~130 microns is 0.66. Under 50% strain compression, its irreversible compression is about 8%, and its vertical thermal conductivity is 62 W / m K.
[0057] Comparative Example 1
[0058] (1) dissolving hydrazine hydrate in water, wherein the mass ratio of hydrazine hydrate to water is 10:100;
[0059] (2) soaking the graphene oxide film in the mixed solution obtained in step (1) and maintaining it at 20°C for 30 minutes to obtain a foamed wet film;
[0060] (3) The foamed wet film obtained in step (2) was naturally air-dried, and low-temperature reduced at 150°C for 24 h, and then placed in a nitrogen atmosphere, heated to 1300°C at 5°C / min and kept at that temperature for 1 h, and then cooled naturally to obtain a foamed carbonized film;
[0061] (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000°C at 5°C / min for 3 h, and then cooled to room temperature to obtain a graphene foamed film.
[0062] The compression rebound curve of the obtained graphene foam film is as follows: Figure 5 As shown, under 50% strain compression, its irreversible compression is about 27%, indicating that its ability to recover shape after compression is poor.
Claims
1. A method for preparing a high-resilience graphene foam film, characterized in that: The following steps are involved: (1) dissolving hydrazine hydrate in a mixed solvent of tert-butyl alcohol and water, wherein the mass ratio of hydrazine hydrate to the mixed solvent is 1-10:100, and the mass ratio of tert-butyl alcohol to water is 2-10:1; (2) Soaking the graphene oxide film in the mixed solution obtained in step (1) at 20-40° C. for 10-30 min to obtain a foamed wet film; (3) drying the foamed wet film obtained in step (2), reducing it at a low temperature of 150-200°C for 10-24 h, then placing it in an inert gas atmosphere, heating it to 1300°C at a rate of 5°C / min and keeping it at that temperature for 1-3 h, and cooling it naturally to obtain a foamed carbonized film; (4) The foamed carbonized film obtained in step (3) is placed in an argon atmosphere, heated to 2000-2600°C at 5°C / min for high temperature treatment for 0.5-3 h, and then cooled to room temperature to obtain a high-resilience graphene foamed film.
2. The preparation method according to claim 1, characterized in that: The thickness of the graphene oxide film in step (2) is between 10 and 100 μm.
3. The preparation method according to claim 1, characterized in that: The carbon-oxygen ratio of the graphene oxide film in step (2) is not greater than 15.
4. The preparation method according to claim 3, characterized in that: The carbon-oxygen ratio of the graphene oxide film in step (2) is 3.5-6.
5. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the graphene oxide film to the mixed solution is not greater than 10%.
6. The preparation method according to claim 1, characterized in that: The graphene oxide film in step (2) is obtained by extruding or casting a graphene oxide slurry and then drying it.
7. The preparation method according to claim 1, characterized in that: The drying method in step (3) is one or more combinations of natural air drying, infrared heating drying, and hot air drying.
8. The preparation method according to claim 1, characterized in that: The inert gas in step (3) is one of nitrogen and argon, or a mixture thereof.
Citation Information
Patent Citations
Graphene porous membrane and preparation method thereof
CN118561272A
Preparation method and application of graphene aerogel fiber woven fabric
CN118621575A